Jumlah Leukosit, Trombosit, dan Kadar Kreatinin Pada Pasien Sepsis Covid-19 Di RSUD Genteng Banyuwangi Pada Periode 2020-2021 - Rezita Nurul Magfiroh; Nur Septia Handayani; Erlinda Widyastuti; Belgis Belgis (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One of the medical conditions that leads to the highest death rate worldwide is sepsis. In the presence of several variables and concomitant conditions, the mortality rate from sepsis keeps rising in proportion to the severity of the condition. It is quite concerning when sepsis patients have proven COVID-19. Some patient subgroups and inflammatory mediators may have increased cytokine release as a result of the SARS-CoV-2 virus. A number of laboratory tests can be used to diagnose COVID-19 and sepsis, one of which is counting leukocytes, platelets, and creatinine levels as indicators of organ failure. The purpose of this study is to characterize the platelet, leukocyte, and creatinine levels in individuals who have been diagnosed with COVID-19 sepsis. This study's methodology employed a descriptive observational technique using 36 patient samples from Genteng Banyuwangi General Hospital, selected based on laboratory examination results (leukocyte count, platelets, and creatinine levels), as well as characteristics related to gender, age, comorbidities, and hospital discharge status. The findings revealed that female patients aged 20 (55.6%) made up the bulk of patients with confirmed COVID-19 sepsis, whereas the largest age group consisted of 9 (56.25%) individuals who were over 60. Twenty-two (61.1%) sepsis patients with proven COVID-19 had a high leukocyte count, and of those with confirmed COVID-19 and sepsis, the majority had normal platelets depending on the platelet count. Nine (56.25%) male patients with confirmed COVID-19 sepsis had elevated creatinine levels, whereas 10 (50%) female patients had normal findings. Patients with sepsis who had verified COVID-19 were generally deceased upon hospital release, with no comorbidities in 14 patients (or 50% of the total), and diabetes mellitus in 13 patients (or 46.4%).